CFD based parametric analysis of gas flow in a counter-flow wet scrubber system - Danzomo, Bashir Ahmed; Salami, Momoh Jimoh Eyiomika; Khan, Md. Raisuddin; Mohd Nor, Mohd Ishkandar (Science Publishing Group, 2013)
Environmental protection measures regarding industrial emissions and tightened regulations for air pollution led to the selection of a counter-flow wet scrubber system based on applicability and economic considerations. The flow dynamics of gas transporting particulate matter and gaseous contaminants is a key factor which should be considered in the scrubber design. In this study, gas flow field were simulated using ANSYS Fluent computational fluids dynamic (CFD) software based on the continuity, momentum and k-ε turbulence model so as to obtain optimum design of the system, improve efficiency, shorten experimental, period and avoid dead zone. The result shows that the residuals have done a very good job of converging at minimum number of iterations and error of 1E-6. The velocity flow contours and vectors at the inlet, across the scrubbing chamber and the outlet shows a distributed flow and the velocity profiles have fully conformed to the recommended profile for turbulent flows in pipes. The total pressure within the scrubber cross-section is constant while the minimum and maximum pressure drops was obtained to be 0.30pa and 3.03pa which has conformed to the recommended pressure drop for wet scrubbers. From the results obtained, it can be deduced that the numerical simulation using CFD is an effective method to study the flow characteristics of a counter-flow wet scrubber system.